2023
DOI: 10.3389/fpsyg.2023.1225850
|View full text |Cite
|
Sign up to set email alerts
|

Measuring what matters in healthcare: a practical guide to psychometric principles and instrument development

Katina Swan,
Renee Speyer,
Martina Scharitzer
et al.

Abstract: The provision of quality healthcare relies on scales and measures with robust evidence of their psychometric properties. Using measurement instruments with poor reliability, validity, or feasibility, or those that are not appropriate for the target diagnostic group or construct/dimension under consideration, may be unfavorable for patients, unproductive, and hinder empirical advancement. Resources from the COnsensus-based Standards for the selection of health status Measurement INstruments (COSMIN) group can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A measure's robust psychometric properties must be demonstrated before implementing it in healthcare or research [11,12]. Two systematic reviews summarising the evidence for the measurement properties of patient self-reported measures developed for people with dysphagia reported poor and incomplete psychometric data [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A measure's robust psychometric properties must be demonstrated before implementing it in healthcare or research [11,12]. Two systematic reviews summarising the evidence for the measurement properties of patient self-reported measures developed for people with dysphagia reported poor and incomplete psychometric data [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…CTT analyses evaluate the performance of a measure as a whole, whereas the IRT framework uses the item as the unit of analysis. Also, contrary to CTT, results in IRT are not bound by the test population [11,19]. Consequently, psychometric studies using CTT analyses may yield different results than studies incorporating IRT principles and, therefore, may lead to different recommendations or guidelines about which measures to implement in clinics or research [10,15,20].…”
Section: Introductionmentioning
confidence: 99%